THE EFFECT OF INFRASTRUCTURE DEVELOPMENT ON ECONOMIC GROWTH IN ASEAN COUNTRIES: DYNAMIC PANEL DATA ANALYSIS - Taufik, Irfan; Markhamah, Siti (PUSAT KEWIRAUSAHAAN UNIVERSITAS BALIKPAPAN, 2024)
This article examines the impact of infrastructure development on economic growth in ASEAN countries using dynamic panel data analysis. The research is motivated by the significant economic transformation in the Southeast Asian region, largely driven by infrastructure development, which has improved connectivity, efficiency, productivity, job creation, and sustainable growth. The analysis considers various sectors including transportation, energy, and communication, and incorporates factors such as education, health, and access to infrastructure. Using the Generalized Method of Moments (GMM) and data from the World Bank from 2002 to 2022, this study investigates the extent to which infrastructure investment contributes to economic growth. The results show a positive and significant relationship between infrastructure development and economic growth, emphasizing the need for policymakers to prioritize infrastructure investment along with institutional reforms to achieve sustainable and inclusive growth. The findings underscore the critical role of infrastructure in improving economic performance and the importance of quality institutions in maximizing the benefits of infrastructure capital in ASEAN countries